Novel foods, food enzymes, and food additives derived from food by-products of plant or animal origin: principles and overview of the EFSA safety assessment - Precup, Gabriela; Marini, Eleonora; Zakidou, Panagiota; Beneventi, Elisa; Consuelo, Civitella; Fernández-Fraguas, Cristina; Garcia Ruiz, Esther; Laganaro, Marcello; Magani, Maura; Mech, Agnieszka; Noriega Fernandez, Estefania; Nuin Garciarena, Irene; et al. (Frontiers in Nutrition, 2024)
The European Union (EU) is committed to transitioning towards a circular economy model with food waste being one of the areas to be targeted. To close the loop of food waste generated during food processing, discarded at the retail or consumption phases, research and innovation parties proposed to valorise agro-food by-products to produce novel foods and food improvement agents (food additives, food enzymes and food flavourings). In the EU, the authorisation of such novel foods and food improvement agents are governed by different regulatory frameworks. A centralised safety assessment by the European Food Safety Authority (EFSA) is the pre-requisite for their authorisation through the so-called Union Lists. Up to December 2023, EFSA published forty-five scientific opinions on the safety of novel foods, food enzymes and food additives derived from by-products of plant and animal origin. The current work aims at illustrating examples of these by-products, for the production of novel foods or food improvement agents and the data requirements behind their respective safety assessment conducted by EFSA. In this review, applications on novel foods, food enzymes and food additives received by EFSA were screened and analysed to find the common scientific requirements and differences in terms of safety evaluation of such products. Various by-products (i.e., corncobs, coffee husks, spent grains of barley and rice, grape pomace, pumpkin peels, bovine whey, eggshells, shrimp heads, animal organs or tissues) were described in the applications, as being processed (extraction, physical treatments, chemical and enzymatic reactions) to obtain novel foods and food improvement agents. The heterogeneity and complexity of these products emphasizes the challenge for their safety assessment, depending on the characteristics of each product. However, as this work shows, the scientific requirements underpinning their safety do not differ substantially in the different regulated product areas considered, with similar information needed to assess their safety, in terms of identity, production process, compositional characterisation, proposed/intended uses and exposure assessment, toxicological information and allergenicity data. Additional nutritional information and data on history of use is required in case of novel foods.